HABITUASI NILAI-NILAI PANCASILA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SMK - Kurniawan, Dony; Karliani, Eli; Ikbal, Asep (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to determine how the habituation of Pancasila values in the learning process and the school environment at SMK YPSEI Palangka Raya in shaping student character. The method used in this research is descriptive research with a qualitative approach. The data collection techniques used by the author in this research are observation, interview and documentation. The results of this study indicate that the habituation of Pancasila values such as in the Learning Process which uses lecture and discussion methods, in-depth questions and answers, group discussions and project methods, as well as strategies used experiential learning, social service activities and authentic assessment. There are two approaches in character building to strengthen the habituation of Pancasila values, namely by giving rewards and punishments. Student Literacy Movement (GLS) which is carried out every morning, Art Activities on Thursdays, Spirituality on Fridays, and Discipline during the learning process. Habituation can change attitudes, both in terms of discipline, activeness, and respect for friends and teachers. The habituation process that is carried out consistently is able to shape the character of students who are more responsible and independent. Students become more disciplined in attending on time, following instructions well, and showing an empathic attitude in their social environment. Obstacles in instilling Pancasila values such as parental factors, student environment, and economic conditions. The learning process cannot be separated from the obstacles in the habituation of Pancasila values such as students who are engrossed in their own world because Civics subjects are often scheduled in the final hours. Distraction from cellphones also has an effect, making students unfocused in participating in learning. Differences in the learning process and the inconsistency of teachers in instilling Pancasila values can hinder the habituation of Pancasila values to students. ABSTRAKPenelitian ini bertujuan untuk mengetahui bagaimana habituasi nilai-nilai Pancasila dalam proses pembelajaran serta lingkungan sekolah di SMK YPSEI Palangka Raya dalam membentuk karakter siswa. Adapun metode yang digunakan dalam penelitian ini adalah jenis penelitian deskriptif dengan pendekatan kualitatif. Adapun teknik pengumpulan data yang dilakukan penulis dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukan bahwa habituasi nilai-nilai Pancasila seperti pada Proses Pembelajaran yang menggunakan metode ceramah dan diskusi, tanya jawab mendalam, diskusi kelompok dan metode projek, serta strategi yang digunakan berbasis pengalaman (experiential learning), kegiatan bakti sosial dan penilaian autentik. Terdapat dua pendekatan dalam pembentukan karakter untuk memperkuat habituasi nilai-nilai Pancasila yaitu dengan pemberian reward dan punishment. Gerakan Literasi Siswa (GLS) yang dilakukan setiap pagi, Kegiatan Kesenian pada hari kamis, Kerohanian pada hari jumat, dan Kedisiplinan saat proses pembelajaran. Habituasi dapat merubah sikap, baik dalam hal kedisiplinan, keaktifan, maupun rasa hormat terhadap teman dan guru. Proses habituasi yang dilakukan secara konsisten mampu membentuk karakter siswa yang lebih bertanggung jawab dan mandiri. Siswa menjadi lebih disiplin hadir tepat waktu, mengikuti instruksi dengan baik, serta menunjukkan sikap empatik dalam lingkungan sosialnya. Kendala dalam menanamkan nilai-nilai Pancasila seperti faktor orang tua, lingkungan siswa, dan keadaan ekonomi. Proses pembelajaran tak lepas terjadi kendala dalam habituasi nilai-nilai Pancasila seperti siswa yang asyik dengan dunianya sendiri karena mata pelajaran PPKn sering dijadwalkan pada jam-jam akhir. Distraksi terhadap handphone turut berpengaruh sehingga membuat siswa tidak focus dalam mengikuti pembelajaran. Perbedaan dalam proses pembelajaran dan tidak konsistennya guru dalam menanamkan nilai-nilai Pancasila dapat menghambat habituasi nilai-nilai Pancasila kepada siswa